A New Technique of Automated Sericulture Based on IoT (International Journal of Innovative Research in Computer Science & Technology, 2022)
Seasonal variations in environmental factors  have a significant impact on genotypic expressions in forms of the phenotypic outputs in silkworm crops, such as a cocoon’s weights, shell’s weights, & cocoon’s shells ratios.  Necessity for the temperature & relatives humilities controls for sustainable cocoon formation is highlight by change in  the environment variables from the day-to-day and the season  to the season. Effect of the temperatures & humid on the  silkworm’s growths & developments, as well as current  findings on heat shock protein, is discussed in depth in this  review study. The impact of air and light on silkworm growth  is also discussed in the study. In addition, the effect of  different environmental variables on the embryonic  developments of the silkworm’s eggs, nutrition indices of the  silkworm’s larvae, & the generative potentials of the  silkworm moths is highlighted in this study. The researchers also discuss need for the cautions when the spinning  silkworm & impacts of the temperatures & humidity on the  silkworm post-cocoon the parameters. Future ideas for  managing climatic conditions for a good cocoon crop were  addressed in the study.
Keywords: Cocoon; IoT; Sericulture; Silk; Temperature